Role of inflammation and eicosanoids in breast cancer. Issue 3 (9th March 2016) - Basu, Samar; Rossary, Adrien; Vasson, Marie‐Paule
Abstract : Mutagenetic and epigenetic influences together with obesity, nutritional, life‐style causes and chronic inflammation are potential risk‐factors for breast cancer. Eicosanoids, namely prostaglandins, leukotrienes and isoprostanes, are biologically potent compounds derived enzymatically or non‐enzymatically from arachidonic acid. Their dynamic role in inflammation and oxidative stress, specifically their interactions with proangiogenic factors in the tumor microenvironment, are well recognized in cancer. Even though the involvement of these compounds is one of the key elements in some types of cancer, knowledge on their role in breast cancer is still limited due to the underlying molecular complexity and hormonal control of breast development and function. This review provides a brief overview of some of the current scientific evidence that recognizes the role of inflammation and eicosanoids in breast carcinogenesis.